1992
DOI: 10.1159/000138986
|View full text |Cite
|
Sign up to set email alerts
|

Protection by a New Synthetic Protease Inhibitor, ONO3307, of the Rat Exocrine Pancreas during Acute Edematous Pancreatitis Induced by a Supramaximal Dose of Caerulein in Comparison with FOY007

Abstract: The present study investigated the protective effects of the new potent synthetic protease inhibitors, ONO3307 (4-sulfamoyl phenyl-4-guanidinobenzoate methanesulfonate) and FOY007 (gabexate misilate), on the exocrine pancreas in rat caerulein-induced acute pancreatitis in both in vitro and in vivo experiments. These protease inhibitors prevented hyperamylasemia, pancreatic edema, congestion of amylase, redistribution of lysosomal enzyme in acinar cells, and lactic dehy-drogenase (LDH) discharge from dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Yoshikawa et al found a protective effect against endotoxin‐induced DIC in rats with 10 or 100 μg/kg/h of ONO‐3307 as measured by fibrin degradation products, number of renal glomeruli with fibrin deposition, and other effects . Likewise, Hirano and others observed beneficial effects of ONO‐3307 in rat acute pancreatitis …”
Section: Plasmin Inhibitors As Antifibrinolyticsmentioning
confidence: 95%
See 4 more Smart Citations
“…Yoshikawa et al found a protective effect against endotoxin‐induced DIC in rats with 10 or 100 μg/kg/h of ONO‐3307 as measured by fibrin degradation products, number of renal glomeruli with fibrin deposition, and other effects . Likewise, Hirano and others observed beneficial effects of ONO‐3307 in rat acute pancreatitis …”
Section: Plasmin Inhibitors As Antifibrinolyticsmentioning
confidence: 95%
“…136 Due to the combined effect on thrombin (coagulation) and plasmin (fibrinolysis), ONO-3307 was tested as a treatment for DIC 137 and pancreatitis. [138][139][140] Yoshikawa et al found a protective effect against endotoxininduced DIC in rats with 10 or 100 μg/kg/h of ONO-3307 as measured by fibrin degradation products, number of renal glomeruli with fibrin deposition, and other effects. 137 Likewise, Hirano and others observed beneficial effects of ONO-3307 in rat acute pancreatitis.…”
Section: Cu-2010mentioning
confidence: 99%
See 3 more Smart Citations